Climate change and the hydropower sector: A global review. (10th January 2022) - Wasti, Asphota; Ray, Patrick; Wi, Sungwook; Folch, Christine; Ubierna, María; Karki, Pravin
Abstract: Renewable sources of electricity, such as solar and wind, need to be paired with sources of reliable baseload. Hydropower is a renewable, low‐emission source of electricity baseload available throughout much of the world as an alternative to electricity conventionally provided by thermal combustion of fossil fuels; however, the global hydropower sector as it stands relies upon surface water flows of substantial and predictable volume. This makes it vulnerable to climate change. The impact of climate change on the hydropower sector is difficult to predict, and not globally uniform. It might be positive, negative, or inconsequential depending upon the local timing and magnitude of changes, reservoir size, allocation priority, and the energy market. The secondary effects of climate change on glacier lake outbursts floods, landslides, and sediment load are poorly understood. In addition, when planning hydropower projects for the future, attention must be given to the greenhouse gas contribution of the impounded waters behind storage dams, and the impact of dams on water temperature. In the past decade, sovereign nations and international development agencies worldwide have evaluated the potential of hydropower as a cost‐effective, clean, sustainable option for baseload electricity supply. There is therefore a crucial need to assess the opportunities and risks hydropower poses across a wide range of potential future climate conditions. This review paper conducts a global survey of the literature on the effect of climate change on hydropower and identifies room for improvement in current approaches to evaluation of the net benefits of hydropower projects under climate change. This article is categorized under: Vulnerability and Adaptation to Climate Change > Learning from Cases and Analogies Assessing Impacts of Climate Change > Evaluating Future Impacts of Climate Change Abstract : The effect of climate change on global hydropower generation, based on observed trends and near‐future projections, is analyzed. The effects are indicated by two levels of symbols: high and low. Generally, if a climate change effect is discussed in more than 50% of the review papers for the region, a "high" symbol (filled in) is adopted. Also shown are the major rivers (blue lines), mountain ranges (cyan hue), and the location of existing and planned hydropower plants (purple dots) (Global Energy Observatory,  2018; Zarfl et al.,  2015).